AN OVERVIEW OF RATIONAL PRESCRIBING PATTERN IN HYPERTENSIVE PATIENTS IN TERTIARY CARE HOSPITAL - Liman, Deepali P.; Mulla, Ashiya; Pawar, Sunita; Diwan, Arundhati (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To study the prescribing patterns of antihypertensive (AHT) drugs in hypertensive (HTN) patients and hypertension with diabetes mellitus (HTN with DM) patients in tertiary care hospital, to assess the rationality of prescribing patterns, to compare the hypertension management with Joint National Committee-7 guidelines (JNC-7). Methods: A prospective study was conducted over a period of 6 mo in the medicine department of Bharati Hospital and Research Centre, Pune. HTN and (HTN with DM patients. Who met the study criteria were enrolled in the study. The pattern of antihypertensive medications prescribed was studied and analyzed using Microsoft excel 2010 and Statistical. The rational prescribing pattern was assessed by using JNC 7 guidelines and World Health Organization (WHO) indicators. Results: Total of 60 patients included in this study, 43 (71.7 %) were HTN patients, and 17 (28.3 %) were HTN with DM patients. There were 29 (48.33 %) males and 31 (51.66 %) female patients were involved. 45 % of patients had pre-hypertension, 33.33 % had stage-1 hypertension, 8.4 % had stage-2 hypertension other 13.33 % patients are on Antihypertensive medications and whose Blood Pressure (BP) were normal according to JNC-7. In hypertensive 47.05 % patient had prescribed Calcium Channel Blockers (CCBs) as monotherapy along with 87.5 % Angiotensin Receptor Blockers (ARBs) with diuretics as combination therapy. In HTN with DM 46.15 % patients had prescribed Angiotensin Converting Enzymes (ACEs) as monotherapy along with 62.5 % CCBs with BBs were prescribed according to JNC-7. As per WHO indicators, average no. of medicines prescribed per prescription was 2.91 and all antihypertensive medicines in the study population were prescribed rationally. Conclusion: The present study represents the current prescribing trend for antihypertensive agents. It implies that. In hypertensive patients ARBs are the leading group of antihypertensive agents as monotherapy and ARBs with diuretics as a combination therapy according to JNC 7. Keywords: Joint National Committee (JNC-7), World Health Organization (WHO), Hypertension (HTN), Diabetes mellitus (DM)